GENE EXPRESSION ANALYSES OF SOME TRANSPOSONS, PHYSIOLOGICAL AND MORPHOLOGICAL CHANGES IN MELON CULTIVARS EXPOSED TO DROUGHT STRESS - S. Çiçek; S. Altıntaş; B. İnal (Journal of Animal and Plant Sciences, 2022)
As sessile organisms, plants are exposed to a wide variety of abiotic and biotic stress. In this case, plants put very complex molecular mechanisms into action against these adverse environmental conditions. Especially at the gene level, it alarms many genes (transcription factors, promoters, miRNA, lncRNA, structural genes, transposons etc.). Transposons, which are among these genes, have recently been studied for their functions. However, it is not known exactly how the plants show the transposons activity, especially in abiotic stress situations. In this respect, expression situations of diverse transposons in plants are still very curious. In this study, various transposon genes belonging to different plant species (tobacco-specific Tto-1, Tto-5 and Tnt-1, Excoecaria agallocha-specific EARE1, rice-specific Tos17, barley-specific BARE1, melon-specific Reme1, Triticum-specific Ttd1a) were used to measure horizontal transfer activities and the expression levels of these transposons were measured by q-RT PCR in sensitive and resistant melon accessions treated with drought stress. Additionally, chlorophyll content, glutathione reductase (GR) activity and some morphometric data were measured in these melon accessions under drought stress. Sensitive and resistant accessions showed significant differences in terms of both gene expression and physiological parameters, indicating the possible role of transposons in drought conditions.
Keywords: Drought; Gene Expression; Melon; Transposon; q-RT PCR